Therapeutic Effects and Biomarkers in Sublingual Immunotherapy: A Review. (5th March 2012) - Fujimura, Takashi; Okamoto, Yoshitaka; Taniguchi, Masaru
Abstract : Immunotherapy is considered to be the only curative treatment for allergic diseases such as pollinosis, perennial rhinitis, asthma, and food allergy. The sublingual route is widely applied for immunotherapy for allergy, instead of the conventional administration by subcutaneous route. A recent meta-analysis of sublingual immunotherapy (SLIT) has shown that this approach is safe, has positive clinical effects, and provides prolonged therapeutic effects after discontinuation of treatment. However, the mechanism of SLIT and associated biomarkers are not fully understood. Biomarkers that change after or during SLIT have been reported and may be useful for response monitoring or as prognostic indicators for SLIT. In this review, we focus on the safety, therapeutic effects, including prolonged effects after treatment, and new methods of SLIT. We also discuss response monitoring and prognostic biomarkers for SLIT. Finally, we discuss immunological mechanisms of SLIT with a focus on oral dendritic cells and facilitated antigen presentation.